Cooperative behaviors and social interactions in the carnivorous bat Vampyrum spectrum - Marisa Tietge; Eduardo Artavia Durán; Mirjam Knörnschild (PLoS ONE, 2025)
Bats exhibit a diverse array of social behaviors, yet detailed studies on the intricacies of these interactions, particularly in rare species like the spectral bat (Vampyrum spectrum), remain scarce. This study presents the first comprehensive description of prey provision and other social behaviors in a wild social group of V. spectrum. Over several months, we conducted extensive video recordings in a hollow tree, used as a day- and night-roost, to document these behaviors, aiming to elucidate key social interactions among the bats and their role within their ecological niche. We observed various remarkable social behaviors, including food provision between family members. Our findings support the hypothesis that prey provision as a form of biparental care may serve as a method for adults to transition young bats from milk to a carnivorous diet, ensuring adequate food intake and allowing them to practice how to handle large prey items. We also challenge the notion that V. spectrum forages exclusively solitarily, as we documented several instances of synchronized roost departures and returns and thus presumably cooperative foraging. This indicates a more complex social structure and behavioral ecology than previously understood. Our comprehensive analysis of observational data enhances our understanding of the social dynamics of V. spectrum, providing new insights into the evolution of cooperative behaviors in bats.